Arthroscopic exploration and biopsy for diagnosis of septic arthritis and osteomyelitis of the coxofemoral joint in a dog - Luther, J. F.; Cook, J. L.; Stoll, M. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
A five-year-old, spayed female mixed breed (38 kg) dog was referred for total hip replacement for an intermittently non-weight bearing lameness of the left hind limb. Radiographs and computed tomography suggested proliferative, osteolytic pathology of the left coxofemoral joint. Using arthroscopic exploration and biopsy, septic arthritis and osteomyelitis in the left coxofemoral joint were diagnosed. Treatment recommendations for antibiotic therapy and femoral head and neck excision were made based upon this diagnosis. Femoral head and neck excision resulted in pain relief and improved function and arthroscopy provided a minimally invasive, yet accurate, diagnosis in this case.*
Keywords: Septic arthritis; osteomyelitis; arthroscopy; coxofemoral joint; dog